Joining up prudential and resolution regulation for systemically important banks - André Ebner; Christiane Westhoff (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2024)
We set out a stylised framework for the policies enacted to address the risks posed by systemically important institutions (SIIs) and to counter the too-big-to-fail (TBTF) problem, examining conceptually how far supervisory and resolution policies are complementary or substitutable. The Financial Stability Board (FSB) TBTF reforms comprise (i) a higher loss-absorbing capacity in the form of regulatory capital buffers for SIIs, (ii) more intensive and effective supervision and (iii) a recovery and resolution regime, including sufficient loss-absorbing and recapitalisation capacity in the form of capital and eligible liabilities, to deal with distressed or failing institutions. These reform strands are part of a fundamentally integrated concept, but were largely developed and implemented independently of each other. Therefore, they may fall short of fully taking interdependencies into account, rendering policies less effective and consistent than an integrated approach, which we outline as an alternative. The analysis discusses the regulatory interplay, its implications for policymaking based on the FSB TBTF reforms for banks and its operationalisation in the Basel framework at the global level and in the European Union.
Keywords: G01; G28; G38; 330; financial regulation; financial stability; going concern; gone concern; macroprudential policy; resolution framework; systemic risk; systemically important institutions; too big to fail